COVID-19-Related Fear and Anxiety: Spiritual-Religious Coping in Healthcare Workers in Portugal - Prazeres, José Filipe Chaves Pereira (2020)
The COVID-19 pandemic has negatively affected the mental health of the general population, and for healthcare workers (HCWs) it has been no different. Religiosity and spirituality are known coping strategies for mental illnesses, especially in stressful times. This study aimed to describe the role of spiritual-religious coping regarding fear and anxiety in relation to COVID-19 in HCWs in Portugal. A cross-sectional quantitative online survey was performed. Socio-demographic and health data were collected as well as the Duke University Religion Index, Spirituality Scale, Fear of COVID-19 Scale, and Coronavirus Anxiety Scale. Two hundred and twenty-two HCWs participated in the study, 74.3% were female and 81.1% were physicians. The median age was 37 years (Q1, Q3: 31, 51.3). Religiosity was neither a significant factor for coronavirus-related anxiety nor it was for fear of COVID-19. Participants with higher levels in the hope/optimism dimension of the Spirituality Scale showed less coronavirus-related anxiety. Female HCWs, non-physicians, and the ones with a previous history of anxiety presented higher levels of fear and/or anxiety related to COVID-19. HCWs’ levels of distress should be identified and reduced, so their work is not impaired.